Status and influencing factors of returning to work 6 months after discharge from hospital with severe acute pancreatitis-a cross-sectional descriptive-analytical study in China - Yang, Dengbi; Quan, Mingtao; Xiao, Xuan (Frontiers in Psychiatry, 2024)
Objective To describe the return to work of patients with severe acute pancreatitis within 6 months after discharge, and to explore the influence of demographic, clinical, and psychosocial factors on their return to work. Research design Prospective 6 months follow-up study. Setting A third class hospital in Guizhou Province. Adult of severe acute pancreatitis(18-60years), with a job before admission, in the intensive care unit ≥ 24 h, were included. Main outcome measures To study return to work and influencing factors one, three and six months severe acute pancreatitis patients discharge. several measurements were used, including General Health Questionnaire (Demographic, disease-related, job-related and health behavior data), Readiness for Return-To-Work Scale and the Hospital Anxiety and Depression Scale. Results Forty-three severe acute pancreatitis patients were included in our study, with mean age 41.53 years. Twenty-nine (67.44%) patients returned to work within 6 months, and fourteen patients did not return to work. The status of Readiness for Return-To-Work Scale: fourteen severe acute pancreatitis patients who did not return to work were mainly in the precontemplation dimension and prepared for action-self-evaluative dimension both 5 cases (35.71%), and the 29 patients who had returned to work were in the Proactive maintenance stage. The study showed that the independent risk factors for returning to work in SAP patients were chronic disease (OR, 0.095; 95% CI [0.011-0.822]; p=0.008), sepsis (OR, 0.071; 95% CI [0.015-0.339]; p=0.009), low education level (OR, 2.905; 95% CI [0.969-8.710]; p<0.001), and anxiety and depression at 6 months (OR, 1.418; 95% CI [0.996-2.019]; p=0.004). Conclusions In conclusion, the return to work of patients with severe acute pancreatitis needs to be improved. Chronic diseases, sepsis, low level of education and higher degree of anxiety and depression at 6 months were important factors leading to their failure to return to work.